MEASUREMENT OF PULSED CURRENT AND VOLTAGE IN PLASMA - Zhukeshov, A. M. (Recent Contributions to Physics, 2017)
The discuss of various aspects of formation and acceleration of plasma streams in pulse guns is carried out on the basis of experimental dates. The depend of current and voltage from pressure in coaxial accelerator KPU-30 is researched.